Purchase Intention as Mediation: SOR Model of Hedonic Lifestyle and Word of Mouth on Purchase Behavior - Haristiyanti, Ratih; Jatmiko, Rohmat Dwi; Fiandari, Yulist Rima (University of Muhammadiyah Malang, 2023)
Consumer purchase behavior is experiencing a rapid change trend, especially with the influence of advances in digitalization. Changes in purchasing behavior are not only customer needs and preferences but also consumer lifestyles. The research examines the effect of a hedonic lifestyle and word of mouth on purchase behavior, with purchase intention as an intervening variable. Data was taken by survey via Google Forms on a sample of 250 using a purposive sampling technique from the customer population of the MS Glow aesthetic clinic. This study used path analysis, and the results show that partially hedonic lifestyle and word of mouth significantly affect purchase intention, hedonic lifestyle and word of mouth affect purchase behavior, and purchase intention significantly affects purchase behavior. Then, purchase intention mediated the effect of a hedonic lifestyle on purchase behavior, and purchase intention mediated the effect of word of mouth on purchase behavior. These findings could help companies design more effective marketing strategies and better understand the relationship between hedonic lifestyles, purchase intent, word of mouth, and consumer behavior. It brings valuable contributions to understanding consumer behavior and successful marketing strategies.